The Pros and Cons of Online Competitive Gaming: An Evidence-Based Approach to Assessing Young Players' Well-Being - Kelly, Sarah; Magor, Thomas; Wright, Annemarie (Frontiers in Psychology, 2021)
This research addresses a lack of evidence on the positive and negative health outcomes of competitive online gaming and esports, particularly among young people and adolescents. Wellbeing outcomes, along with mitigation strategies were measured through a cross sectional survey of Australian gamers and non-gamers aged between 12 and 24 years, and parents of the 12 to 17-year-olds surveyed. Findings revealed potential benefits for light gamers including mental and physical wellbeing. Adverse health consequences were associated with heavy gaming, suggesting that interventions that target moderated engagement could be effective. It provides timely insights in an online gaming landscape that has rapidly evolved over the past decade to include the hyper-connected, highly commercialized and rapidly growing esports sector.